2014
DOI: 10.1002/pro.2428
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variation and structural conservation allows development of novel function and immune evasion in parasite surface protein families

Abstract: Trypanosoma and Plasmodium species are unicellular, eukaryotic pathogens that have evolved the capacity to survive and proliferate within a human host, causing sleeping sickness and malaria, respectively. They have very different survival strategies. African trypanosomes divide in blood and extracellular spaces, whereas Plasmodium species invade and proliferate within host cells. Interaction with host macromolecules is central to establishment and maintenance of an infection by both parasites. Proteins that me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 53 publications
3
45
0
Order By: Relevance
“…This interaction can lead to different responses, such as lack of recognition (molecular disguise or mimicry) or active immune depression of the host . Both processes have been well described in Steinernema feltiae , and it has been demonstrated that the cuticle/epicuticle of this EPN, particularly its lipid moieties, actively interferes with both humoral and cellular responses of G. mellonella larvae …”
Section: Discussionmentioning
confidence: 99%
“…This interaction can lead to different responses, such as lack of recognition (molecular disguise or mimicry) or active immune depression of the host . Both processes have been well described in Steinernema feltiae , and it has been demonstrated that the cuticle/epicuticle of this EPN, particularly its lipid moieties, actively interferes with both humoral and cellular responses of G. mellonella larvae …”
Section: Discussionmentioning
confidence: 99%
“…Endothelial tethering is mediated by the P. falciparum erythrocyte membrane protein 1, PfEMP1, a large protein family with ∼60 members encoded in each genome [13,14]. Each PfEMP1 is formed from multiple copies of two parasite-specific domain types, the CIDR and DBL domains, which are most often spatially arranged in a linear array (Figure 1) [15]. Different individual domains are capable of interacting with specific human endothelial surface proteins, including endothelial protein C receptor, EPCR [16], intracellular adhesion molecule 1, ICAM-1 [17] and cluster of differentiation 36, CD36 [18].…”
Section: Do Anti-disease Immunogens Have a Place In Future Malaria Vamentioning
confidence: 99%
“…Antigenic variation in T. brucei was discussed by P. Borst in the previous version of this book, Mobile DNA II (7), and therefore we will attempt in this chapter to update that report by reviewing the findings that have been published since then. For more detailed discussion of specific aspects of T. brucei antigenic variation, the reader is referred to several recent reviews (21)(22)(23)(24)(25)(26)(27).…”
Section: Antigenic Variation In Trypanosomesmentioning
confidence: 99%
“…In fact, VSG appears to function solely as an antigen and does not perform any important biochemical activity, meaning that it is remarkably free to vary in sequence, with different functional VSGs sharing as little as 20% primary sequence identity (36). Still, there are clearly some limitations to VSG structure because all VSGs identified to date share strong features of secondary structure (37), in particular long α helices, which presumably stand perpendicular to the plasma membrane and contribute to the intact coat's depth and density (26,38).…”
Section: Antigenic Variation In Trypanosomesmentioning
confidence: 99%
See 1 more Smart Citation